Method of Structural Design of Heavy Machine Tools. (2016) - Kovalov, Viktor; Antonenko, Yana; Dašić, Predrag
Abstract: This paper presents a method of arrangement the frames of heavy lathes with dispersed forces along the coordinate axes of the loads that act on the machine while it is running. Mathematical models of large bearing systems, taking into account typical and boundary loads are developed. The field trials of the action of frames are conducted. We analyzed the movement of the frame on the coordinate axes due to its loading. A solid modeling and research of support of heavy lathe using a package Solid Works Simulation are conducted. The perspective ways to further improve the accuracy of machine tools are proposed.